Peptides: Basic determinants of reproductive functions - Celik, Onder; Aydin, Suleyman; Celik, Nilufer; Yilmaz, Musa (Elsevier Science Inc, 2015)
Mammalian reproduction is a costly process in terms of energy consumption. The critical information regarding metabolic status is signaled to the hypothalamus mainly through peripheral peptides from the adipose tissue and gastrointestinal tract. Changes in energy stores produce fluctuations in leptin, insulin, ghrelin and glucose signals that feedback mainly to the hypothalamus to regulate metabolism and fertility. In near future, possible effects of the nutritional status on GnRH regulation can be evaluated by measuring serum or tissue levels of leptin and ghrelin in patiens suffering from infertility. The fact that leptin and ghrelin are antagonistic in their effects on GnRH neurons, their respective agonistic and antagonistic roles make them ideal candidates to use instead of GnRH agonist and antagonist. Similarly, kisspeptin expressing neurons are likely to mediate the well-established link between energy balance and reproductive functions. Exogenous kisspeptin can be used for physiological ovarian hyperstimulation for in-vitro fertilization. Moreover, kisspeptin antagonist therapy can be used for the treatment of postmenapousal women, precocious puberty, PCOS, endometriosis and uterine fibroids. In this review, we will analyze the central mechanisms involved in the integration of metabolic information and their contribution to the control of the reproductive function. Particular attention will be paid to summarize the participation of leptin, kisspeptin, ghrelin, NPY, orexin, urocortin, VIP, insulin, galanin, galanin like peptide, oxytocin, agouti gene-related peptide, and POMC neurons in this process and their possible interactions to contribute to the metabolic control of reproduction. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Peptides; Reproduction; Infertility